Comparison of thermal bridge calculation methods - Balázs Nagy; Martin Marosvölgyi; Zsuzsa Szalay (Acta Polytechnica CTU Proceedings)
We need to consider linear heat losses due to thermal bridges for the accurate calculation of building heat losses. Our research examined a whole building, and different thermal bridge calculation methods were compared. The following techniques were included in the study: a simplified method according to the Hungarian energy performance regulation where the effect of thermal bridges can be taken into account by multiplication factors applicable to thermal transmittances; a simplified thermal bridge catalogue of ISO 14683; a recent national thermal bridge catalogue; two-dimensional thermal modelling as well as a conjugated heat and moisture (HAM) simulation considering steady-state and dynamic conditions. Overall, we created eight different numerical modelling approaches depending on the type of simulation and boundary condition. The modelling and simulations were carried out using multiphysics software based on the finite element method according to ISO 10211 and EN 15026. All the relevant details of the building were analysed to get a complete picture. Based on the results, we analysed each method's relative proportions of surface and linear heat losses. The evaluation showed that the Hungarian simplified method generated the lowest heat losses for thermal bridges, while ISO 14683 produced the highest results, with the numerically simulated results in the middle. The overall heat losses varied by 30 %, depending on the thermal bridge calculation method. Linear heat losses were between 12 % to 32 % of the surface heat losses. Our study helps to choose the adequate method to perform thermal bridge simulations.